Preparation of high-quality FeV50 alloy by an improved SHS-EAH multi-stage process. Issue 10 (15th May 2023) - Yu, Bin; Yuan, Tiechui; Shi, Junjie; Qiu, Yuchao; Jiang, Chenglong; Wu, Xiaoping; Xiao, Daihong; Li, Ruidi; Jing, Han; Ye, Mingfeng
Abstract: As the most widely used vanadium intermediate alloy, ferrovanadium is mainly prepared by the self-propagating high-temperature synthesis (SHS) process with the advantages of short process and large heat release. However, there is a trade-off between the amount of reduction agent of Al and the product quality of ferrovanadium, which is caused by the thermodynamic equilibrium limitation of the reduction between Al and vanadium oxides. The reasonable adjustment of the trade-off has become an urgent problem to be solved for the preparation of high-quality ferrovanadium. In the present work, the thermodynamic equilibrium for the reduction limitation using Al as reducing agent has been thoroughly analyzed with the reference to the equilibrium phase diagram. It was found that the theoretical reduction limitation of total vanadium (T.V) in slag was decreased from 4.08 wt.% to wt. 0.86 wt.% when the Al content in alloy reached 2.0 wt.% at 1800 °C. The vanadium in slag was mainly presented in the form of MgV3 O8 and coexisting with other phases of MgAl2 O4, CaAl2 O4, CaAl4 O7, CaAl12 O19 . With the purpose of further decrease the high Al concentration in alloy and vanadium loss in slag, an improved SHS-EAH process was implemented by multi-stage gradient aluminum addition coefficient pattern, the average vanadium content in slag was reduced from 1.82 wt.% to 0.83 wt.%, while the aluminum content in FeV50 alloy was decreased from 1.5 wt.% to 0.4 wt.%. The SHS-EAH process was proved to be a better process with improved yield and quality for the preparation of ferrovanadium.